STUDENT PUBLIC SPEAKING PRACTICES THROUGH CULTUM AND DA'I CILIK: A CASE STUDY IN CLASS IV ELEMENTARY SCHOOL - Faracha Nur Rahma; Almuntaqo Zainuddin (Universitas Majalengka, 2023)
The ability to speak in front of a general audience or public speaking needs to be trained as early as possible. Public speaking will provide many benefits for someone to continue to achieve a better career in the future. The purpose of this research is to analyze how public speaking is practiced at MIM PK Wirogunan through the Islamic lecture and young preachers’ program that have been implemented since 2015/2016. This study uses a type of qualitative research with a case study research design. The number of respondents used was 7 people consisting of school principals, teachers in class IV A and B, and 2 students each in class A and B. The research data presented was in the form of descriptions accompanied by quotes from the results of interviews conducted with the respondents. This research took place using data collection techniques through three ways, namely observation, interviews, and documentation. Data analysis was carried out through three stages, namely data reduction, data presentation, and conclusions. The validity test was carried out by means of technique and source triangulation. The results of the study show that the two programs implement the expected form of public speaking training, namely the fulfillment of public speaking components such as speakers, material recipients, material content, and feedback. Positive impacts were also received by students, namely having a more courageous mentality, self-confidence, and being able to think more critically. However, there are also a number of obstacles that have been encountered, but so far, they have been handled well through evaluation activities. Kemampuan berbicara di depan khalayak umum atau public speaking perlu dilatih sedini mungkin. Public speaking akan memberikan segudang manfaat untuk kelangsungan seseorang mencapai karier yang lebih baik di masa mendatang. Penelitian ini bertujuan untuk menganalisa bagaimana praktik public speaking di MIM PK Wirogunan melalui program kultum dan da’i cilik yang telah dilaksanakan sejak tahun 2015/2016. Penelitian ini menggunakan jenis penelitian kualitatif dengan desain penelitian studi kasus. Jumlah responden yang digunakan berjumlah 7 orang yang terdiri dari kepala sekolah, guru kelas IV A dan B, serta masing-masing 2 siswa kelas A dan B. Data penelitian yang disajikan berupa deskripsi yang disertai kutipan hasil wawancara bersama responden. Penelitian ini berlangsung menggunakan teknik pengumpulan data melalui tiga cara yaitu observasi, wawancara, dan dokumentasi. Analisis data yang dilakukan melalui tiga tahapan yakni reduksi data, penyajian data, serta kesimpulan. Uji keabsahan yang dilakukan adalah dengan cara triangulasi teknik dan sumber. Hasil penelitian menunjukkan bahwa kedua program tersebut mengimplementasikan bentuk pelatihan public speaking yang diharapkan, yakni hampir terpenuhinya komponen public speaking seperti adanya pembicara, penerima materi, isi materi, serta adanya feedback. Dampak positif juga diterima siswa yakni memiliki mental lebih berani, percaya diri, serta mampu berpikir lebih kritis. Akan tetapi terdapat pula beberapa kendala yang turut ditemui, namun sejauh ini dapat diatasi dengan baik melalui kegiatan evaluasi.